Association of Heart Rate Turbulence With Arrhythmia Susceptibility and Heart Disease in Mice. (11th September 2015) - STÖCKIGT, FLORIAN; JÜNGST, PHILIPP; LINHART, MARKUS; NICKENIG, GEORG; ANDRIÉ, RENÉ; BEIERT, THOMAS; SCHRICKEL, JAN WILKO
Heart Rate Turbulence in Mice: Introduction: Recent studies have demonstrated the feasibility of measuring heart rate turbulence (HRT) as a marker of baroreflex function in healthy mice. The aim of this investigation was to measure HRT in a mouse model with induced structural heart defects and to determine if there were threshold values of HRT for inducible ventricular tachycardias (VTs). Methods and Results: HRT was measured during electrophysiological investigations 2 weeks after transverse aortic constriction (TAC, n = 13) or myocardial cryoinfarction (MCI, n = 14). Sham‐operated mice served as controls (n = 8 for TAC controls and n = 9 for MCI controls). Mice with heart disease lacked an early acceleration (turbulence onset [TO]) in heart rate after extrastimulus pacing (heart disease: 0.39% [0.19%–0.59%] vs. all controls: –0.04% [–0.25—0.19%]; P < 0.01). At a cutoff value of >0.25%, TO could be used to classify mice with induced heart disease with a sensitivity of 64.0% and specificity of 88.2% (P < 0.01) but did not identify mice at higher risk of induced VTs. Animals that were susceptible to VTs (n = 8) had lower values for turbulence slope (TS) compared with noninducible mice (6.2 milliseconds/beat [3.1–9.5 milliseconds/beat] vs. 10.1 milliseconds/beat [7.2–14.2 milliseconds/beat]; P = 0.03). TS <7.8 milliseconds/beat identified mice with inducible VTs with a sensitivity of 75.0% and specificity of 75.8% (P = 0.02). Conclusion: Measurement of HRT is feasible in mouse models with induced structural heart disease. More abnormal values for TO were found in the presence of structural heart disease but did not predict susceptibility to VTs. Decreased TS was associated with VTs induced by programmed stimulation.